Perceived effectiveness rating scales applied to insomnia help-seeking messages for middle-aged Japanese people: a validity and reliability study - Machi Suka; Takashi Yamauchi; Hiroyuki Yanagisawa (Komiyama Printing Co. Ltd, 2017)
Abstract Background Communicating health messages is an important way to influence people's behaviors towards health issues. Providers need to incorporate audience's perspective to design more persuasive messages. This study aimed to develop rating scales for measuring audience's perception of effectiveness of health messages in Japanese people. Methods The comprehensibility scale including five items and the persuasiveness scale including seven items were designed based on literature review. A cross-sectional web-based survey was conducted among Japanese adults aged 35-45 years to assess the reliability and validity of the scales. Participants were asked to rate a text message that encouraged help-seeking intention for insomnia. All scale items were scored on a 1-to-5 point Likert scale, and they were averaged to produce an overall score for each scale. Results Explanatory factor analysis revealed a two-factor solution that agreed with the comprehensibility and persuasiveness scales, respectively. Correlation coefficients between each set of items ranged between 0.63-0.87 for the comprehensibility scale and 0.37-0.76 for the persuasiveness scale. Cronbach alpha (0.88) indicated satisfactory internal consistency of the set of items. The mean (SD) of the comprehensibility and persuasiveness scores were 3.70 (0.82) and 3.15 (0.61), respectively, without ceiling or floor effects. These scores were significantly associated with intended future use of the message. The proportion of participants who reported a positive help-seeking intention for insomnia was significantly higher in the higher score groups for both scales. Multiple logistic regression analysis showed that the comprehensibility and persuasiveness scores were significantly associated with the help-seeking intention for insomnia. Conclusion The proposed rating scales exhibited adequate reliability and validity for measuring the comprehensibility and persuasiveness of insomnia health-seeking message in middle-aged Japanese people. Further studies are needed to confirm the generalizability of the results, but these scales may be useful for pretesting a health message with audience members to make it more acceptable and persuasive to the intended audience. Trial registration Not applicable; this is not a report of intervention trial.